FREQUENCY AND INTENSITY OF LOW BACK PAIN IN PARTICIPANTS IN A FITNESS CORPORATE PROGRAM (Fiep Bulletin - online, 2014)
Low back pain is one of the biggest causes of employee absenteeism. In Brazil, 56.89% of the individuals have this problem, being withdrawn from work for a period of time, provoking economic damages. The majority of back injuries are in the lumbar region (70%), followed by the thoracic (11%), and the cervical ones (7%). The most frequent causes of pain in the lumbar region are: protusion or hernia of the intervertebral cord, injury of soft parts, bone breaking and disc malnutrition. Among the important risk factors for its occurrence are sedentary lifestyle, few hours of sleep, and long periods in a seated position. The present research was developed in a Brazilian company that has a Health Promotion Centre (HPC) with regular physical activities and nutritional orientation. The objective of the study was to quantify low back pain frequency and intensity, comparing the practitioners' status before and after enrollment at a systematic program of physical activities, performed under professional's supervision. A suitable questionnaire of a model validated for the World Health Organization (WHO) was applied. The sample comprised 57 participants, being 34 participants in the HPC and a control group with 23 non-engaged clients. After a two-month period, a reduction in the low back pain frequency was verified, passing from a value of 3.01 that represented 50% of pain during the week, to one of 2.16 (25%). Besides the statistical analysis evidencing an important difference between the attributed values before and after training, an alteration in the low back pain frequency was also recorded, which did not happen in the control group. As to its intensity, besides the statistical evidence, a qualitative improvement was observed in the practitioners: 2.87 (Moderate Pain) for 2.07 (Little Pain).
Keywords: Low back pain; quality of life; corporate fitness